The Significance and Advancement of Digital Competencies in Human Capital Management - Dernowska-Żaczyk, Natalia; Smarżewska, Daria (Znaczenie i rozwój kompetencji cyfrowych w zarządzaniu kapitałem ludzkim, 2025)
Aim: The objective of this article is to identify the significance and conditions for the development of digital competencies in human capital management within enterprises. Methodology: A quantitative research approach was applied using the CATI (Computer-Assisted Telephone Interviewing) technique and a proprietary survey questionnaire. The study was conducted in enterprises operating in Poland with both domestic and foreign capital. Basic statistical tools were used to analyse the empirical data. Results: The analysis revealed several barriers to the development of digital competencies, including lack of time and awareness of their importance, resistance to change, and difficulties in identifying necessary skills. The growing relevance of digital skills for enterprise operations was underscored. Implications and recommendations: The limitations of the study include its pilot nature (47 enterprises), which may affect the representativeness of the findings. Another limitation is the subjective nature of the respondents’ self-assessments. The authors recommend extending future research to a larger and more diverse sample and incorporating qualitative methods. Originality/value: The article presents original research on the development of digital competencies in human capital management, providing a basis for future expansions.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 2, s. 38-49